2020
DOI: 10.1016/j.metabol.2020.154396
|View full text |Cite
|
Sign up to set email alerts
|

UCP1-dependent and UCP1-independent metabolic changes induced by acute cold exposure in brown adipose tissue of mice

Abstract: Background: Brown adipose tissue (BAT) is a site of metabolic thermogenesis mediated by mitochondrial uncoupling protein 1 (UCP1) and represents a target for a therapeutic intervention in obesity. Cold exposure activates UCP1-mediated thermogenesis in BAT and causes drastic changes in glucose, lipid, and amino acid metabolism; however, the relationship between these metabolic changes and UCP1-mediated thermogenesis is not fully understood. Methods: We conducted metabolomic and GeneChip array analyses of BAT af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 71 publications
(95 reference statements)
3
47
0
1
Order By: Relevance
“…Clearly, the pathways affected by acute cold mostly involved amino acid metabolism and the citric acid cycle. Interestingly, several of these metabolic pathways were also affected in brown adipose tissue (BAT) after 2–6 h of cold exposure in mice: alanine and aspartate metabolism [ 16 ]; alanine, aspartate and glutamate metabolism; glycine, serine and threonine metabolism; and pyruvate metabolism and the citric acid cycle (TCA) [ 8 ]. It is important to note that several amino acids in rodent BAT seemed to be regulated in the opposite direction when compared with the changes in human plasma related to cold exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the pathways affected by acute cold mostly involved amino acid metabolism and the citric acid cycle. Interestingly, several of these metabolic pathways were also affected in brown adipose tissue (BAT) after 2–6 h of cold exposure in mice: alanine and aspartate metabolism [ 16 ]; alanine, aspartate and glutamate metabolism; glycine, serine and threonine metabolism; and pyruvate metabolism and the citric acid cycle (TCA) [ 8 ]. It is important to note that several amino acids in rodent BAT seemed to be regulated in the opposite direction when compared with the changes in human plasma related to cold exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, methionine, isoleucine and valine were all increased in BAT after 4–6 h of cold exposure [ 8 ] and serine and threonine increased in BAT after 4–6 [ 8 ] and 12 h [ 17 ] of acute cold exposure in non-acclimatized mice, but they all decreased or had a trend to decrease (isoleucine) in plasma of cold-acclimatized humans after ice-water swimming. Similarly, levels of 15 out of 19 amino acids measured after 4 h cold exposure (4 °C) were increased in BAT of wild-type mice [ 16 ]. This could indicate that the decrease in plasma amino acids may reflect their uptake and utilization by BAT in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reduction in the expression level of this gene over the course of time in cold conditions suggests the possibility of a switch in the mechanism associated with metabolic changes in BAT. A recent study showed that cold conditions induce UCP1 dependent/independent thermogenesis in BAT [ 28 ]. The reduction in the expression of ATGL under acute cold conditions further supports that under acute cold conditions the process of lipolysis in BAT is not dependent on ATGL[ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The classical method is cold exposure. Acute cold exposure (10°C, 4 h) induces UCP1-mediated thermogenesis-dependent glucose utilization by affecting amino acid metabolism in BAT 109 . Chronic cold exposure (6°C, 10 days) has also been shown to activate glucose oxidation in BAT and WAT browning 110 .…”
Section: Potential Therapeutic Applications In Batmentioning
confidence: 99%